Improvement of anaerobic digestion of sewage sludge in a wastewater treatment plant by means of mechanical and thermal pre-treatments: Performance, energy and economical assessment. (January 2015) - Ruffino, Barbara; Campo, Giuseppe; Genon, Giuseppe; Lorenzi, Eugenio; Novarino, Daniel; Scibilia, Gerardo; Zanetti, Mariachiara
Highlights: The efficiency of AD on WAS in the largest Italian WWTP has to be improved. Mechanical and low-temperature thermal pre-treatments were tested. Thermally treated samples produced from 20% to 30% more methane than untreated samples. Low-temperature thermal pre-treatments caused a significant decrease in WAS viscosity. Total revenues from electricity sale raised by 10% compared to the present scenario. Abstract: Performances of mechanical and low-temperature (<100 °C) thermal pre-treatments were investigated to improve the present efficiency of anaerobic digestion (AD) carried out on waste activated sludge (WAS) in the largest Italian wastewater treatment plant (2, 300, 000 p.e.). Thermal pre-treatments returned disintegration rates of one order of magnitude higher than mechanical ones (about 25% vs. 1.5%). The methane specific production increased by 21% and 31%, with respect to untreated samples, for treatment conditions of respectively 70 and 90 °C, 3 h. Thermal pre-treatments also decreased WAS viscosity. Preliminary energy and economic assessments demonstrated that a WAS final total solid content of 5% was enough to avoid the employment of auxiliary methane for the pre-treatment at 90 °C and the subsequent AD process, provided that all the heat generated was transferred to WAS through heat exchangers. Moreover, the total revenues from sale of the electricity produced from biogas increased by 10% with respect to the present scenario.